Hereditary hemochromatosis and risk of joint replacement surgery: A systematic review and meta-analysis - Karn Wijarnpreecha (2022)
Background/Objectives: Arthritis is a known manifestation of hereditary hemochromatosis. However, whether patients with hereditary hemochromatosis have an increased risk of having joint replacement surgery compared to the general population is still unknown. This meta-analysis was conducted to better characterize this risk. Methods: A comprehensive literature review was conducted utilizing the MEDLINE and EMBASE databases through September 2019 to identify all cohort studies that compared prevalence or incidence of joint replacement surgery (hip, ankle, or knee) between patients with hereditary hemochromatosis and individuals without hereditary hemochromatosis. Effect estimates from each study were extracted and combined together using the random-effect, generic inverse variance method of DerSimonian and Laird. Results: A total of five studies with 1 293 407 participants fulfilled the eligibility criteria and were included in the meta-analysis. Overall, the risk of having joint replacement surgery was significantly increased in patients with hereditary hemochromatosis compared to individuals without hereditary hemochromatosis with the pooled relative risk (RR) of 3.32 [95% confidence interval (CI), 1.60-6.86; I288%]. Analysis by joint found a significantly increased risk of having hip and ankle replacement surgery among patients with hereditary hemochromatosis compared with the pooled RR of 2.62 (95% CI, 2.09-3.30; I247%) and 8.94 (95% CI, 3.85-20.78; I214%), respectively. The risk of having knee replacement surgery was also increased but was not statistically significant (pooled RR 1.57, 95% CI, 0.83-2.98; I266%). Conclusions: A significantly increased risk of needed joint replacement surgery among patients with hereditary hemochromatosis compared to patients without hereditary hemochromatosis was demonstrated in this study. Further studies are required to determine whether this association is causal.